Rural Education and Chemistry teaching: experiments in schools of the countryside in the Mato Grosso state - Marcos Antonio Oliveira Rodrigues; Mariuce Campos de Moraes; Nilbea Soares Pereira (Universidade Federal do Norte do Tocantins, 2020)
Rural Schools are faced with multiple challenges, among them to guarantee a Chemistry teaching based on the local reality, which gives access to Science without losing the sociocultural characteristic of each community. Problematized by such a challenge, this article deals with experiences carried out during the course Bachelor of Sciences (Major: Chemistry) and promoted by the articulation between Undergraduate Studies and Extension Projects. The study aims to report and reflect on two experiences within a Rural School ("Escola do Campo", in Brazil), and to analyze how the approach of different themes is pertinent to the specificities of Rural Education. In this investigation, the report on experiences is considered as a methodological strategy that enables a reflexive analysis of our educational practice. Workshops were carried out, divided by thematic approach. In the first workshop entitled "Cleaning with Chemistry" seventeen students took part; The second workshop, entitled "Water and Its Importance", had twenty-six participants. On the one hand, we recognize that we discuss a previously established subject matter, which remains far from the school curriculum and the specific conditions of the local context, on the other hand, we perceive thematic advances and challenges with the problematization of pertinent topics of rural living, in the sense of a scientific training, and of the social valorization of the struggles of rural living.